Liderazgo orientado a la gente en call centers - León, Federico R. (2017)
Purpose: Call centers generate stress and absenteeism in staff and the literature suggests that people-oriented leadership is the right way of supervision for such a situation. This study compared its effects versus those of other types of leadership. Methodology: Absentee data of 379 representatives of customer services of a Peruvian call center were analyzed and the representatives answered a questionnaire about the Framework of Values in Competition and its four types of leadership. Day and night work shifts were compared. Results: It was observed that absenteeism declines with people-oriented leadership, although only during the day shift, and the addition of leadership oriented to change, results and control devalues models. Limitations/implications: Future studies should cover the performance of the worker. The findings suggest a need to re-focus the theoretical focus on environmental contingencies that affect leadership effectiveness. Originality/value: Leadership theorists will ask themselves in what circumstances the multiple leadership is effective. Call center managers will appreciate the organizational value of people-oriented leadership at the first level of supervision.